Cost evaluation of PAGE-B risk score guided HCC surveillance in patients with treated chronic hepatitis B - Martin F. Sprinzl; Christina Feist; Sandra Koch; Wolfgang M. Kremer; Karl J. Lackner; Arndt Weinmann; Peter R. Galle (BMC, 2021)
Abstract Background The PAGE-B score (Platelet Age GEnder-HBV) selects chronic hepatitis B (cHB) patients showing no relevant 5-year risk for hepatocellular carcinoma (HCC). We, therefore, explored potential cost reduction following the introduction of a PAGE-B tailored ultrasound screening in a single center cohort of cHB patients receiving stable antiviral therapy. Methods cHB patients attending throughout the year 2018 were documented. Patients eligible for PAGE-B score were classified into high (≥18 points), intermediate (10-17 points) and low (≤9 points) HCC risk groups. Patients of the low HCC risk group could postpone HCC screening to reduce HCC screening expenses. Full costs for hepatic ultrasound were assessed. Results Throughout the year cHB patients (n = 607) attended our clinic, which included PAGE-B eligible patients (n = 227, 37.4%) of whom n = 94 (15.8%) were allocated to the low HCC risk group. Sonographic HCC screening during a median exam time of 12.4 min (IQR 9.2-17.2) resulted in total costs of 22.82 Euro/exam. Additional opportunistic expenses caused by patient's lost earnings or productivity were 15.6-17.5 €/exam and 26.7 €/exam, respectively. Following a PAGE-B tailored HCC screening at our institution annual full costs for cHB patients could be reduced by 15.51%, which equals a cost reduction by 1.91% for our total sonography unit. In comparison, 1.35% up to 7.65% of HBV-infected patients of Caucasian descent could postpone HCC screening according to population-based estimates from Germany. Conclusions PAGE-B risk score adapted screening for HCC is an efficient and cost neutral tool to reduce costs for sonography in Caucasian patients with chronic hepatitis B receiving antiviral treatment.